The Most Effective Functioning of Competitive Supply Chain Pricing Based on Social Responsibility Dimensions: A Case Study of Oil Products of Knowledge-Based Companies - Hayder Dhahir Mohammed; Zahra Hayati Bahadorani; Neda Fallah; Erfan Seyyedi; Hayder Mahmood Salman; Hakimeh Morabbi Heravi (Discrete Dynamics in Nature and Society)
In today’s competitive environment, taking the advantage of supply chain which is both effective and efficient is a competitive advantage. An adequate supply chain has a multifaceted structure that focuses on integrating all factors, including pricing. The final product is delivered to customers based on maintaining market values and increasing strategic interactions. Present study aims to present the most effective functioning of competitive supply chain pricing in accordance with aspects of social responsibility. In doing so, we conducted a case study on oil-related products of Iranian knowledge-based companies. A combined analysis with 15 university-level industrial management experts was employed in this study to establish the components (competitive supply chain pricing function) and research propositions (dimensions of social responsibility). Twenty managers of knowledge-based enterprises in the oil field evaluated the components and propositions identified in the form of matrix questions using interpretative rating (IRP). The results showed that the proposition of the ethical dimension is the most effective measure of the social responsibility of knowledge-based companies in the oil field, creating competitive supply chain pricing functions based on value. This result shows that, under the ethical dimension of social responsibility, processes of competitive supply chain pricing are formed in accordance with the customer values and, according to the strategic relationship between the company and the economy with regional and global partners, maintaining values are a critical factor in developing our interactions between pricing factors. Given the results, in the first step for success, knowledge-based companies are recommended to consider the priorities of professional ethics in addition to knowledge in order to be able to gain the trust of customers by understanding their functional nature in the country’s developing economy. In this situation, the pricing process based on the creation of comprehensive values for customers can help to increase the company’s competitive position and make these companies to be at the first level of strategic interactions with companies that use petroleum products.